An international study of hospitalized cancer patients’ health status, nursing care quality, perceived individuality in care and trust in nurses: A path analysis - Charalambous, Andreas; Radwin, Laurel E.; Berg, Agneta C.; Sjövall, Katarina; Patiraki, Elisabeth; Lemonidou, Chryssoula; Katajisto, Jouko K.; Suhonen, Riitta A. (My University, 2016)
Background Providing high quality nursing care for patients with malignancies is complex and driven by many factors. Many of the associations between nursing care quality, trust, health status and individualized care remain obscure. Objective To empirically test a model of association linking hospitalized cancer patients’ health status, nursing care quality, perceived individuality in care and trust in nurses. Design A cross-sectional, exploratory and correlational study design was used. Settings This multi-site study was conducted in cancer care clinics, in-patient wards of five tertiary care hospitals in Cyprus, Finland, Greece and Sweden. Sample Out of 876 hospitalized patients with a confirmed histopathological diagnosis of cancer approached to participate in the study in consecutive order, 599 (response rate 68%) agreed to participate and the data from 590 were used for path analysis. Methods Data were collected in 2012–2013 with the Individualized Care Scale-Patient (ICS-Patient), the Oncology Patients’ Perceptions of Quality Nursing Care Scale (OPPQNCS), the Euro-Qol (EQ-5D-3L) and the Trust in Nurses Scale. Data were analysed statistically using descriptive and inferential statistics. Mplus version 7.11 was used to determine the best Trust model with path analysis. Results Although the model fit indices suggested that the hypothesized model did not perfectly to the data, a slightly modified model which includes the reciprocal path between individualized care and nursing care quality demonstrated a good fit. Conclusion A model of trust in nurses was developed. Health status, individualized care, and nursing care quality were found to be associated with trust. The model highlights the complexity of caring for cancer patients. Trust in nurses is influenced by the provision of individualized care. Generating and promoting trust requires interventions, which promote nursing care quality, individuality and patients’ health status.
Keywords: Health status; In-patients; Individualized care; Modelling; Nursing care; Oncology; Trust in nurses; Path analysis; Quality